1999
DOI: 10.1152/ajpheart.1999.276.3.h1091
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic, mitogenic, and angiogenic actions of UTP on vascular endothelial cells

Abstract: Endothelial cells express receptors for ATP and UTP, and both UTP and ATP elicit endothelial release of vasoactive compounds such as prostacyclin and nitric oxide; however, the distinction between purine and pyrimidine nucleotide signaling is not known. We hypothesized that UTP plays a more important role in endothelial mitogenesis and chemotaxis than does ATP and that UTP is angiogenic. In cultured endothelial cells from guinea pig cardiac vasculature (CEC), both UTP and vascular endothelial growth factor (VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 29 publications
5
38
0
1
Order By: Relevance
“…40 P2Y 4 receptors were identified on spontaneously hypertensive rat (SHR)-derived cultured rat aortic smooth muscle cells, perhaps coupled to mitogenesis via P42/P44 mitogen-activated protein kinase (MAPK). 41 Although these and other studies have reported that UTP is equipotent with ATP in producing mitogenesis of vascular smooth muscle, 37,[42][43][44][45] a recent report has claimed that UTP, unlike ATP, has an antiproliferative action on human arterial and venous smooth muscle cells derived from internal mammary artery and saphenous vein. 46 There is no obvious explanation for this discrepancy.…”
Section: P2 Receptorsmentioning
confidence: 98%
See 1 more Smart Citation
“…40 P2Y 4 receptors were identified on spontaneously hypertensive rat (SHR)-derived cultured rat aortic smooth muscle cells, perhaps coupled to mitogenesis via P42/P44 mitogen-activated protein kinase (MAPK). 41 Although these and other studies have reported that UTP is equipotent with ATP in producing mitogenesis of vascular smooth muscle, 37,[42][43][44][45] a recent report has claimed that UTP, unlike ATP, has an antiproliferative action on human arterial and venous smooth muscle cells derived from internal mammary artery and saphenous vein. 46 There is no obvious explanation for this discrepancy.…”
Section: P2 Receptorsmentioning
confidence: 98%
“…97 In cultured endothelial cells from guinea pig cardiac vasculature, UTP and VEGF were mitogenic and chemotactic factors. 44 The possibility that UTP was acting indirectly via VEGF was not examined.…”
Section: P2 Receptorsmentioning
confidence: 99%
“…In this study, we examined the mechanism of Rho activation and Rho-dependent stress fiber formation mediated by the P2Y 2 nucleotide receptor (P2Y 2 R), an integrin-associated GPCR activated by ATP or UTP that mediates stress fiber formation and chemotaxis in a variety of cell types (Bagchi et al, 2005;Kaczmarek et al, 2005;Satterwhite et al, 1999;Sauzeau et al, 2000;Wang et al, 2005) and plays an important role in monocyte (Seye et al, 2002) and neutrophil homing (Chen et al, 2006) to injured or infected tissues. Previously, we found that an RGD integrin-binding domain in the first extracellular loop of the P2Y 2 R enables the receptor to interact with ␣v␤3 and ␣v␤5 integrins and this interaction is prevented by mutation of the RGD sequence to RGE (Erb et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the role of P2Y receptors (P2YRs) in angiogenesis with only a handful of reports providing evidence supporting this notion. We have shown earlier that P2YR signaling promotes angiogenic properties such as endothelial cell tubulogenesis (Rumjahn et al, 2007), whereas others have reported P2YR-mediated migration (Satterwhite et al, 1999;Kaczmarek et al, 2005) and permeability (Tanaka et al, 2004(Tanaka et al, , 2006. Activated P2Y 2 receptors can transactivate vascular endothelial growth factor receptor-2 (VEGFR-2), suggesting a direct link between extracellular nucleotides and established tumour angiogenesis signaling (Seye et al, 2004).…”
mentioning
confidence: 99%